PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATERI POLA BILANGAN UNTUK KELAS VIII SMP - Mutia Utari (Departemen Matematika, 2022)
The purpose of this research is to produce interactive learning media for class VIII students' number pattern material that is valid and practical as one of the learning media for class VIII number pattern material so that it can make it easier for students to understand the lesson.. This interactive learning media uses the Plomp development model which consists of 2 stages, namely the preliminary research and prototyping phase. The subjects of this research were 9 students of class VIII SMPN 13 Padang. The instruments used are validation sheets and questionnaires. In this research, a valid and practical mathematical e-module was obtained. The e-module is valid with 83,88% results in the very valid category. A The results of the questionnaire for the student questionnaire, the practicality value of 84,79% was obtained in the very practical category. Keywords– Development, Interactive Learning Media, Practical, Valid